Public opinion on economic globalization : considering immigration, international trade, and foreign direct investment - White, Roger, 1967- (Palgrave Macmillan, 2017)
This book examines survey data to consider the extent to which public support for immigration, international trade, and foreign direct investment exists in a cohort of 38 heterogeneous countries. With economic globalization shaping daily life, understanding the determinants of public opinion is crucial for policy makers. This timely volume uses survey data from the Pew Research Center's 2006-2014 Global Attitudes Project (GAP) in conjunction with data from several secondary sources. White identifies the factors that underlie the reluctance of some members of the public, and some societies, to view these topics in a more positive light. Specifically, he considers the roles of culture, cultural differences ("cultural distance"), and relative social and economic development as determinants of public opinion and corresponding cross-societal differences of opinion